2022
DOI: 10.3389/fmicb.2021.816845
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Biochemical Properties of a GH46 Chitosanase From Marine Streptomyces hygroscopicus R1 Suitable for Chitosan Oligosaccharides Preparation

Abstract: Due to the various biological activities of chitosan oligosaccharides (COSs), they have great potential value for use in many areas. Chitosanase plays an important role in enzymatic preparation of COSs. Herein, a gene encoding a chitosanase (ShCsn46) from marine Streptomyces hygroscopicus R1 was cloned and the sequences encoding ShCsn46 without signal peptide were optimized based on the codon usage of Pichia pastoris (P. pastoris). In addition, the optimized gene was ligated to pPICZαA and transformed to P. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…According to the previous studies, we found that the pH stability of chitosanases from GH46 family varies greatly in accordance with their sources. The chitosanases from S. avermitilis , B. mojavensis SY1, and S. hygroscopicus R1 were stable from pH 4.0 to 8.0 ( Guo et al, 2021 ; Wang et al, 2021a , b ). Additionally, the residual activity of chitosanases from Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the previous studies, we found that the pH stability of chitosanases from GH46 family varies greatly in accordance with their sources. The chitosanases from S. avermitilis , B. mojavensis SY1, and S. hygroscopicus R1 were stable from pH 4.0 to 8.0 ( Guo et al, 2021 ; Wang et al, 2021a , b ). Additionally, the residual activity of chitosanases from Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the cold adaptive chitosanase from G. sunshinyii is only stable at the temperature from 5 to 35°C ( Qin et al, 2018a ). In addition, the chitosanases from S. hygroscopicus R1and B. amyloliquefaciens are mesophilic enzyme, which are stable at the temperature in the range from 35 to 55°C ( Luo et al, 2020 ; Wang et al, 2021b ). However, the thermal stable chitosanase from Streptomyces roseolus displays higher residual activity even though the incubating temperature reached 65°C ( Jiang et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations